(untitled) (Global Journal of Human-Social Science, 2020)
The paper is aimed at e xamining relation bet ween factors determining export behavior and propensity to innovate to fill Afghanistan specific literature gap. For this purpose, a number of 236 small and medium manufacturing firms were targeted as statistical unit of analysis. Required data were collected through questionnaire distributed to owner/manager of firms. Descriptive statistics as well as multivariate probit regression were utilized to analyze the data. Findings confirmed no significant relationship between export behavior and propensity to innovate. It further suggests that marketing innovation and technological advancement positively and significantly influence export behavior and propensity to innovate. Furthermore, and unlike result of many other similar studies there was insignificant influence of firm size and firm age on propensity to innovation.